Globalizing transitional justice : contemporary essays - Teitel, Ruti G. (Oxford University Press, 2014)
Among the most prominent and significant political and legal developments since the end of the Cold War is the proliferation of mechanisms for addressing the complex challenges of transition from authoritarian rule to human rights-based democratic constitutionalism, particularly with regards to the demands for accountability in relation to conflicts and abuses of the past. Ruti G. Teitel provides a collection of her own essays that embody her evolving reflections on the practice and discourse of transitional justice since her book 'Transitional Justice' published back in 2000.